ALGEBRAIC APPROACH TO INFORMATION FUSION IN ONTOLOGY-BASED MODELING SYSTEMS - Artemieva, Irina; Zuenko, Alexander; Fridman, Аlexander (International Journal of Computing, 2014)
In this paper we discuss the possibilities to use algebraic methods (in particular, n-tuple algebra developed by the authors) to improve the functioning of convenient ontology-based modeling systems. An illustrative example shows the ways to unify representation and processing of two major parts of subject domain ontologies